To simplify the expression \(2 \times 5 \left( \frac{16}{2} - 2 \times 3 \right) - 2\), follow these steps:
-
Simplify inside the parentheses: \[ \frac{16}{2} = 8 \] \[ 2 \times 3 = 6 \] Therefore, the expression inside the parentheses becomes: \[ 8 - 6 = 2 \]
-
Substitute this back into the expression: \[ 2 \times 5 (2) - 2 \]
-
Simplify the multiplication: \[ 2 \times 5 = 10 \] Then replace into the expression: \[ 10 \times 2 - 2 \]
-
Continue simplifying: \[ 10 \times 2 = 20 \] Finally, subtract 2: \[ 20 - 2 = 18 \]
Thus, the simplified result is: \[ \boxed{18} \]